Analisis Implementasi Fatwa DSN-MUI No.04 dengan Pendekatan Systematic Literature Review (SLR) - Dhimas Ulil Albab; Muhammad Ridhwan Sidiq; Muhammad Zaki Alhafidz (Journal of Fiqh in Contemporary Financial Transactions, 2026)
This study aims to analyze the implementation of murabahah financing in Islamic financial institutions in Indonesia in relation to its compliance with the DSN-MUI Fatwa No. 04/DSN-MUI/IV/2000. The research method employed is a Systematic Literature Review (SLR) by systematically analyzing relevant studies published between 2021 and 2025 that examine murabahah practices in Islamic commercial banks, Islamic rural banks (BPRS), Baitul Maal wat Tamwil (BMT), and Sharia Savings and Loan Cooperatives (KSPPS). The findings indicate that although murabahah financing has normatively referred to the provisions of the DSN-MUI fatwa and PSAK 102, practical implementation still reveals indications of non-compliance, particularly concerning asset ownership, transparency of cost price and profit margin, and the substantive nature of the contract. The novelty of this study lies in its comprehensive mapping of recent literature findings regarding deviations in murabahah practices across various types of Islamic financial institutions. In conclusion, the implementation of murabahah financing in Indonesia requires stronger reinforcement of sharia compliance to ensure conformity with both the principles and substance of the contract as stipulated in the DSN-MUI fatwa.